2020
DOI: 10.1002/mds.28173
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Antioxidants and Risk of Parkinson's Disease in the Singapore Chinese Health Study

Abstract: A BS TRACT: Background: Despite experimental evidence implicating oxidative stress in the pathogenesis of PD, epidemiological studies have provided inconsistent associations between dietary antioxidants and risk of developing PD. Furthermore, no study has been done in any Asian population. Objectives: We examined the associations for intake levels of dietary carotenoids (α-carotene, β-carotene, lycopene, β-cryptoxanthin, and lutein) and vitamins (vitamin A, C and E) and the risk of developing PD. Methods: We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 59 publications
1
17
0
1
Order By: Relevance
“…Four studies included in our study about vitamin A with the risk of PD (3 case–control studies and 1 cohort study): all showed there were no preventive benefits of dietary vitamin A to PD. [ 19 , 32 , 35 , 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…Four studies included in our study about vitamin A with the risk of PD (3 case–control studies and 1 cohort study): all showed there were no preventive benefits of dietary vitamin A to PD. [ 19 , 32 , 35 , 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…Potential PD cases among the cohort participants were identified from three independent sources 4 . First, three follow‐up interviews were conducted on all surviving cohort participants from 1999 to 2004 (n = 52,322), 2006 to 2010 (n = 39,528), and 2014 to 2016 (n = 17,105).…”
Section: Methodsmentioning
confidence: 99%
“…Potential PD cases among the cohort participants were identified from three independent sources. 4 First, three follow-up interviews were conducted on all surviving cohort participants from 1999 to 2004 (n = 52,322), 2006 to 2010 (n = 39,528), and 2014 to 2016 (n = 17,105). Participants were asked if they had ever been informed by a physician to have PD and, if yes, the age at which the diagnosis was ascertained.…”
Section: Case Ascertainmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies will be needed to explore and compare other brain areas for a similar type of activity. Additionally, a Singaporean Chinese cohort-based study also suggested no correlation between dietary antioxidants, such as carotenoids and vitamins (vitamin A, C, and E), and risk of developing PD [57]. A comparative study suggested the relation between risk of PD and intake of carotenoids, VitE and VitC.…”
Section: Vitamins Based Clinical Studies In Parkinson's Diseasementioning
confidence: 99%